2015
DOI: 10.1007/s10741-015-9480-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac amyloidosis: the great pretender

Abstract: Cardiac amyloidosis (CA) is often misdiagnosed because of both physician-related and disease-related reasons including: fragmented knowledge among different specialties and subspecialties, shortage of centres and specialists dedicated to disease management, erroneous belief it is an incurable disease, rarity of the condition, intrinsic phenotypic heterogeneity, genotypic heterogeneity in transthyretin-related forms and the necessity of target organ tissue histological diagnosis in the vast majority of cases. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 35 publications
2
129
0
16
Order By: Relevance
“…This approach can be challenging, especially in context of large scale population-based screening. EMB is a procedure often restricted to centers with significant expertise in its performance, typically large referral centers with transplant programs 1 . While rare, procedural complications can include arrhythmia, perforation with pericardial tamponade, and pneumothorax 22 .…”
Section: Classical Diagnostic Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach can be challenging, especially in context of large scale population-based screening. EMB is a procedure often restricted to centers with significant expertise in its performance, typically large referral centers with transplant programs 1 . While rare, procedural complications can include arrhythmia, perforation with pericardial tamponade, and pneumothorax 22 .…”
Section: Classical Diagnostic Testsmentioning
confidence: 99%
“…Amyloidosis is caused by extracellular deposition of abnormal protein fibrils, resulting in destruction of tissue architecture and impairment of organ function 1 . Amyloidosis may be localized or systemic, and is categorized by the type of precursor protein 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cardiac phenotype is typically either HCM or RCM and the condition may be inherited (usually due to mutations in transthyretin, TTR) or associated with immunoglobulin light-chain depositiontermed AL amyloidosis. 88 Elevated cardiac Tn levels are associated with a poor prognosis in AL amyloidosis and are routinely used to stage the disease and stratify treatment. 89,90 The role of troponins in wild type TTR related amyloid (ATTR) is less well established but a recent study found levels TnI were higher in patients with ATTR amongst a heart failure with persevered ejection fraction (HFpEF) population.…”
Section: Amyloid Cardiomyopathymentioning
confidence: 99%